Transfers from Earth to LEO and LEO to interplanetary space using lasers. (May 2018) - Phipps, Claude R.; Bonnal, Christophe; Masson, Fréderic; Boustie, Michel; Berthe, Laurent; Schneider, Matthieu; Baton, Sophie; Brambrink, Erik; Chevalier, Jean-Marc; Videau, Laurent; Boyer, Séverine A.E.
Abstract: New data on some materials at 80ps pulse duration and 1057 nm wavelength give us the option of proportionally combining them to obtain arbitrary values between 35 (aluminum) and 800 N/MW (POM, polyoxymethylene) for momentum coupling coefficient C m . Laser ablation physics lets us transfer to LEO from Earth, or to interplanetary space using repetitively pulsed lasers and C m values appropriate for each mission. We discuss practical results for lifting small payloads from Earth to LEO, and space missions such as a cis-Mars orbit with associated laser system parameters. Highlights: New approach to launching small payloads into low Earth orbit, or interplanetary orbit from LEO. 25 kg flyer is a sphere of laser ablation fuel surrounding payload, discarded at end of mission. Mass fraction m/M up to 61% delivered to LEO, a factor-of-10 improvement over chemical rockets. Mass fraction m/M of 54% for launching an inspection craft to GEO and 35% launching to Mars from LEO. An application is monitoring global climate using constellations of Earth-observing microsats.